Ta’līm Qawā’id al-Lugah al-Arabiyah fī Kullīyati al- Syarī’ah bi Jāmi’ati Maulānā Mālik Ibrāhīm al- Islāmiyah al-Hukūmiyah Malang bi Barmajiyah “Arabunā” - Ma'arif, A. Samsul (Journal of Language Intelligence and Culture, 2020)
The process of learning Arabic in Indonesia has yet to achieve satisfactory results. This is evidenced by the sincerity of the Arabic Teachers and Lecturers to be creative and continuously improve the learning process, by providing the existence of good and interesting learning media. Arobuna Program is one of the Arabic grammar learning media (qawaid) specifically designed for beginners in learning qawaid. Researchers tried to uncover the effectiveness of this program in learning Arabic grammar (qawaid) in PKPBA students of the Arabic Special Lecture Program) Faculty of Sharia UIN Maulana Malik Ibrahim Malang. This article aims to; (1) describe the advantages and disadvantages of the Arobuna program; (2) describe the procedures for using the Arobuna program; and (3) find out the learning effects arising from the presence of the Arobuna program. The data used in this study came from field observations and examinations. Researchers analyzed the data as it was proposed by Lexy Meleong. The results of this study indicate that; (1) Arobuna program used in the learning process of Arabic grammar (qawaid) on PKPBA students of the Faculty of Sharia UIN Maulana Malik Ibrahim Malang have advantages and disadvantages; (2) the Arobuna program in learning requires three steps namely preparation, planning and assessment; and (3) Students who have studied using Arobuna media have good Arabic language skills.